The model of the wooden gunstock of handheld short barrel bombard in late 14 early 15th century from Lviv History Museum collection - Verkhoturova, Mariana (Lviv Polytechnic Publishing House, 2016)
This article presents detailed description of the cast-iron short barrel bombard in late 14 early 15th century from Lviv History museum collection. Briefly analyzed some options of the wooden gunstock cannon, developed and described the wooden gunstock of the handheld bombard.
Keywords: handheld short barrel bombard; wooden gunstock; model; Lviv History Museum